Pelatihan Pemanfaatan Platform Penjualan dalam Meningkatkan Kinerja UMKM di Kecamatan Ilir Barat II Kota Palembang - Dessy Yunita; Welly Nailis; Ahmad Maulana; M. Eko Fitrianto (Penerbit Goodwood, 2023)
Purpose: Training on the Use of Sales Platforms in Improving Small Medium Enterprise (SME) Performance in Kecamatan Ilir Barat II, Palembang City is provided for entrepreneurs to understand the best marketing techniques through a digital context. Methodology: Entrepreneurs are equipped with the ability to learn, understand and choose the type of sales platform that helps their business grow. The Participants were provided with knowledge through lecture and presentation methods after which MSME assistance was provided after the training. Results: The training provided to entrepreneurs, especially in Kecamatan Ilir Barat II, Palembang City has a significant impact on market expansion in the future. Conclusions: The Sales Platform can be used for any type of business, whether small or large companies. Limitations: The limitations of the operator network are an obstacle in the process of implementing the community service. In addition, the different levels of participants' ability to absorb the training material. Contribution: The community service is related to marketing management science, especially promotion